Impact of possible tardive dyskinesia on physical wellness and social functioning: results from the real-world RE-KINECT study - Caroline M. Tanner; Stanley N. Caroff; Andrew J. Cutler; William R. Lenderking; Huda Shalhoub; Véronique Pagé; Ericha G. Franey; Michael Serbin; Chuck Yonan (SpringerOpen, 2023)
﻿Abstract Background Tardive dyskinesia (TD) is a persistent and potentially disabling movement disorder associated with antipsychotic use. Data from RE-KINECT, a real-world study of antipsychotic-treated outpatients, were analyzed to assess the effects of possible TD on patient health and social functioning. Methods Analyses were conducted in Cohort 1 (patients with no abnormal involuntary movements) and Cohort 2 (patients with possible TD per clinician judgment). Assessments included: EuroQoL's EQ-5D-5L utility (health); Sheehan Disability Scale (SDS) total score (social functioning); patient- and clinician-rated severity of possible TD ("none", "some", "a lot"); and patient-rated impact of possible TD ("none", "some", "a lot"). Regression models were used to analyze the following: associations between higher (worse) severity/impact scores and lower (worse) EQ-5D-5L utility (indicated by negative regression coefficients); and associations between higher (worse) severity/impact scores and higher (worse) SDS total score (indicated by positive regression coefficients). Results In Cohort 2 patients who were aware of their abnormal movements, patient-rated TD impact was highly and significantly associated with EQ-5D-5L utility (regression coefficient: − 0.023, P < 0.001) and SDS total score (1.027, P < 0.001). Patient-rated severity was also significantly associated with EQ-5D-5L utility (− 0.028, P < 0.05). Clinician-rated severity was moderately associated with both EQ-5D-5L and SDS, but these associations were not statistically significant. Conclusions Patients were consistent in evaluating the impacts of possible TD on their lives, whether based on subjective ratings ("none", "some", "a lot") or standardized instruments (EQ-5D-5L, SDS). Clinician-rated severity of TD may not always correlate with patient perceptions of the significance of TD.